Progressive Multifocal Leukoencephalopathy in a 62-Year-Old Immunocompetent Woman - Venkata C. Gourineni; Tristan Juvet; Yogesh Kumar; Doru Bordea; Kanaga N. Sena (Case Reports in Neurological Medicine)
Progressive multifocal encephalopathy (PML) is a rare demyelinating disease that typically presents in immunodeficient patients. We report a case of a previously healthy 62-Year-Old woman who suffered from an unsteady gait, throbbing headaches, and progressive left-sided weakness and numbness. Stroke was initially suspected based on imaging and symptoms. A series of follow-up magnetic resonance images of the brain showed a right parietal lesion growing in size as the patient became unable to walk and experienced increasing lethargy and confusion. A biopsy of the lesion was positive for the John Cunningham virus (JCV). A diagnosis of PML was made and she was started on mefloquine. No improvement was seen on this treatment and her condition worsened. Although PML remains uncommon in immunocompetent individuals, it cannot be ruled out based on their immune status. Although the exact cause remains uncertain, underlying or transient states of immunosuppression may be responsible for reactivation of the JCV in these patients.